MENGOPTIMALKAN PEMBELAJARAN PAI MELALUI DESAIN MEDIA PEMBELAJARAN YANG KREATIF DI SD MUHAMMADIYAH 24 SURABAYA - Firnanda, Nabella Enita Putri; Fitria Balqis, Aida; Nofa Sagita, Irfan; Yusron Maulana El-Yunusi, Muhammad (IAIN Bone, 2024)
AbstractAt SD Muhammadiyah 24 there are symptoms that students feel bored with teachers when they explain lesson material using the lecture method. This is because if the lecture method is used continuously, students will become bored and not focus on the lesson material. However, if the lecture method is alternated with the use of audio-visual media such as flipbooks and PowerPoint, students will be more focused in the learning process because it is fun and they will not feel bored. The research was conducted at SD Muhammadiyah 24 Surabaya. Research subjects included school principals, teachers and students. Observations were carried out at the site to get a real picture of how to optimize PAI learning through creative design of learning media. Comprehensive interviews were conducted to find out the problems and solutions used. Based on the results of interviews with teachers, cooperative learning makes it easier for students to receive information from their classmates or other friends because they are not embarrassed or reluctant to ask questions. Based on the results of the author's interviews with teachers, the learning media implemented at SD Muhammadiyah 24 Surabaya uses types of learning media such as PowerPoint and flipbooks. The final result is that optimizing PAI learning can be achieved through cooperative learning and the use of interactive teaching methods based on lecture, PowerPoint and flipbook learning media. These strategies can improve students' understanding, social skills, collaboration and self-confidence. Teachers must be creative and innovative in using learning media to actively involve students in the learning process.Â